1993
DOI: 10.1016/0014-5793(93)81789-3
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear‐encoded polypeptide Cfo‐II from spinach is a real, ninth subunit of chloroplast ATP synthase

Abstract: Proton-translocating F-ATP synthases from chloroplasts contain a nuclear-coded subunit, CFo-II, that lacks an equivalent in the corresponding E. coil complex. Three recombinant phages that code for the entire precursor of this subunit have been isolated from 2 gtl 1 cDNA expression libraries made from polyadenylated spinach RNA using a two-step strategy. The reading frame of 222 amino acid residues includes 147 residues for the mature protein (M r 16.5 kDa) and a transit sequence of 75 residues (M r 8.0 kDa). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…In contrast the F 1 F 0 ATP synthase from photosynthetic prokaryotes contains two different b subunits [50][51][52]. Now it is evident that even ancient non-photosynthetic eubacteria can possess two different b subunits.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast the F 1 F 0 ATP synthase from photosynthetic prokaryotes contains two different b subunits [50][51][52]. Now it is evident that even ancient non-photosynthetic eubacteria can possess two different b subunits.…”
Section: Discussionmentioning
confidence: 99%
“…However, a very different mechanism has been demonstrated for three other thylakoid proteins: subunit II of the integral CF o component of the thylakoidal ATP synthase (CF o II) and subunits X and W of photosystem II (PSII-X and PSII-W). These proteins are synthesized with bipartite presequences that strongly resemble typical Sec-type signal peptides (22)(23)(24), yet they integrate into thylakoid membranes in the absence of stromal factors, nucle-* The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
mentioning
confidence: 99%
“…The TargerP [30] and Predotar [31] programs predicted that ATPG protein is targeted to chloroplast. Sequence alignment showed that the ATPG homologs existed in various plants, including Spinacia [15], Vitis vinifera, Oryza sativa, Populus trichocarpa, Sorghum bicolor and Physcomitrella patens. In addition, the homologs were also found in Volvox carteri, Chlamydomonas reinhardtii and Cyanophora paradoxa (Figure 1(a)).…”
Section: The Nuclear Atpg Gene Encodes the Subunit II Of Chloroplast mentioning
confidence: 99%
“…Although the construction and function of subunit b in E. coli have been studied in great detail [13,14], the knowledge about subunits II and I of chloroplast ATP synthase is limited. The nuclear atpG gene encoding the subunit II of chloroplast ATP synthase has been thought to be a duplication of atpF encoding the subunit I [15], but the secondary structures of two subunits are different significantly. In Spinach, the subunit II is shorter than subunit I and it has been predicted to contain less -helix [12].…”
mentioning
confidence: 99%